Immunohistochemistry of thyroid gland carcinomas: clinical utility and diagnostic pitfalls. Issue 5 (May 2016) - Chernock, Rebecca D.
Abstract: There are several settings in which immunohistochemistry could be employed in thyroid pathology. Ancillary immunohistochemistry can aid in differentiating tumour types and has also been used to support a diagnosis of malignancy in equivocal follicular lesions. Theoretically, immunostains could serve as prognostic markers as well. Here, we focus on the role of immunohistochemistry as a diagnostic tool mainly in less well-differentiated carcinomas, to confirm cell lineage. In this setting, it is important to perform a panel of immunostains and interpret them in the context of the tumour morphology and the clinical picture, since staining patterns can overlap with other non-thyroid tumour types. We also address the controversial use of immunostains to separate malignant from benign follicular lesions. Lastly, the potential for immunohistochemistry as prognostic markers will be considered. This review emphasizes the application of immunohistochemistry to thyroid histopathology rather than cytology.